Hydrostatic pressure-tuning of photoelectric properties of perovskite Cs2SeI6 through first-principles investigation. (December 2022) - Hu, De-Yuan; Zhao, Xian-Hao; Tang, Tian-Yu; Li, Li; Tang, Yan-Lin
Abstract: Pressure engineering can produce a inner change and atoms redistribution for perovskite Cs2 SeI6 . As a result, the photoelectric properties of perovskite Cs2 SeI6 would be varied under different pressure conditions. Base on the density functional theory (DFT), the photoelectric properties of perovskite Cs2 SeI6 under different hydrostatic pressure have been investigated by using the first-principles. The lattice constant, unit cell volume and bond length of perovskite Cs2 SeI6 are significantly reduced with the increase hydrostatic pressure. Moreover, perovskite Cs2 SeI6 has the optimal optical bandgap value of 1.34 eV under a pressure of 1.5 GPa. Therefore, we only study the photoelectric properties of Cs2 SeI6 when the hydrostatic pressure is 0 and 1.5 GPa in this paper. The calculated results show that Cs2 SeI6 is stable under the pressure of 0 GPa and 1.5 GPa according to the calculations of Born-Huang stability criterion and phonon dispersion spectrum. It can be found that perovskite Cs2 SeI6 are all soft, ductile and anisotropic before and after pressure. In addition, when the hydrostatic pressure is 1.5 GPa, perovskite Cs2 SeI6 has larger values of dielectric functions, absorption coefficient and optical conductivity. This study indicates that perovskite Cs2 SeI6 is an excellent photovoltaic material after applied hydrostatic pressure, which has great potential in application of perovskite solar cells. Graphical Abstract: Crystal structure of perovskite Cs2 SeI6 . ga1